Influência dos hormônios sexuais nas respostas ventilatórias, termorreguladoras e na concentração de monoaminas de ratos e ratas - Marques, Danuzia Ambrozio (Universidade Federal de São Carlos, 2019)
Evidences in the literature show differences between sexes in the control of ventilation and in the prevalence of respiratory disorders such as sleep apneas or hypopneas, that occurs three times more in men than women. Sex-specific differences are also observed in body temperature control (Tb) since women present changes through the menstrual cycle. Those differences between sexes in both Tb and ventilation suggest a possible role of gonadal hormones in the respiratory control, which can act on microglial cells and peripheral or CNS receptors that, in turn, control the respiratory network. Additionally, it is known that the main monoamines, dopamine (DA), noradrenaline (NOR) and serotonin (5-HT), are neurotransmitters that participate in ventilation and thermoregulation control acting in CNS regions such as the medial preoptic area of the hypothalamus (MPA), Locus coeruleus (LC), and bulbar raphe, which in turn, present sex-specific differences. Thus, our study aimed to evaluate the influence of the main sex hormones on ventilation and body temperature as well as to quantify the monoamines in the raphe, MPA and LC of male and female rats during hypercapnia and hypoxia conditions. We also evaluated the morphological characteristics of the microglia cells in intact and ovariectomized (OVX) rats under normocapnia and hypercapnia in CNS regions involved with ventilation control. We showed that orchiectomy (ORX) decreases ventilation during normocapnic-normoxia and testosterone (T) replacement was able to restore it as well as changing the chemosensitivity to hypoxia and hypercapnia without altering the metabolism or body temperature of animals. In females, hormonal fluctuations during the estrous cycle did not change the ventilatory and metabolic parameters during hypoxia, however, OVX decreases the ventilatory response of animals by 40% and hormone replacement did not restore this response. Besides, we demonstrate that sex hormones influence the quantification of monoamines (and their metabolites) in response to hypercapnia and hypoxia in LC, bulbar raphe and MPA in intact and castrated male and female Wistar rats. Finally, we showed that ovarian hormones could prevent microglial reactivity in CO2/H+ sensitive structures in females. Thus, taken together, we described that there are sex-related differences in male and female ventilatory control, as well as in the quantification of monoamines in LC, MPA and Raphe nucleus. We also demonstrate that in females microglia cells respond to both OVX and hypercapnia in regions that participate in ventilatory control.
Influence of sex hormones on ventilation, thermoregulation and in monoamine concentrations of male and female rats
Keywords: Dimorfismo-sexual; Catecolaminas; Pletismografia; Reposição hormonal; Castração; Microglia; CNS; Sexual dimorphism; Catecholamine; Punch; HPLC-ED; Plethysmography; Hormone replacement; Castration; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA DA RESPIRACAO; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA ENDOCRINA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA GERAL